2022
DOI: 10.1093/narcan/zcac006
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum is associated with inflammation and poor survival in early-stage HPV-negative tongue cancer

Abstract: Persistent pathogen infection is a known cause of malignancy, although with sparse systematic evaluation across tumor types. We present a comprehensive landscape of 1060 infectious pathogens across 239 whole exomes and 1168 transcriptomes of breast, lung, gallbladder, cervical, colorectal, and head and neck tumors. We identify known cancer-associated pathogens consistent with the literature. In addition, we identify a significant prevalence of Fusobacterium in head and neck tumors, comparable to colorectal tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Specifically, an abundance of Fusobacterium nucleatum and Porphyromonas gingivilis is clinically correlated with poor survival in HNSCC in a site-specific manner. 40,102 Poor survival outcomes with Fusobacterium abundance has been also previously reported in colorectal cancer, wherein the authors proposed development of preventive and treatment strategies targeting intestinal microflora by probiotics and antibiotics. 103 Use of antibiotics in colorectal adenocarcinoma in-vivo models have shown to have positive impact on disease outcomes and in preventing metastases.…”
Section: Clinical and Therapeutic Relevance Of Microbiome In Hnsccmentioning
confidence: 84%
“…Specifically, an abundance of Fusobacterium nucleatum and Porphyromonas gingivilis is clinically correlated with poor survival in HNSCC in a site-specific manner. 40,102 Poor survival outcomes with Fusobacterium abundance has been also previously reported in colorectal cancer, wherein the authors proposed development of preventive and treatment strategies targeting intestinal microflora by probiotics and antibiotics. 103 Use of antibiotics in colorectal adenocarcinoma in-vivo models have shown to have positive impact on disease outcomes and in preventing metastases.…”
Section: Clinical and Therapeutic Relevance Of Microbiome In Hnsccmentioning
confidence: 84%
“…As a foil to this limitation, we were encouraged to see a recent example of a robust sample collection method described in Desai et al ( 2022 ); these authors specified that their OSCC data was derived from only fresh-frozen primary tumors of tongue origin. We recommend that such specific criteria become the norm for studies in this field.…”
Section: Analysis Of Results and Discussionmentioning
confidence: 99%
“…In oral cancer, specifically tongue cancer, F. nucleatum was associated with poor survival, nodal metastases and extracapsular spread [56 ▪ ]. Interestingly, a recent study by Neuzillet et al reported contradictory results where F. nucleatum was associated with lower recurrence rate, significantly longer overall survival, relapse-free and metastasis-free survival [57].…”
Section: Fusobacteria As a Biomarker For Cancer Diagnosis And Prognosismentioning
confidence: 99%